Experimental Study of Explosion Characteristics and General Correlations of Lean H2/CO/CH4/Air Mixtures in Quiescence. (13th February 2023) - Nguyen, Minh Tien; Bui, Van Ga; Nguyen, Xuan Bao; Nguyen, Le Chau Thanh; Pham, Minh Man; Truong, Thi Hoa; Phung, Minh Tung; Bui, Van Hung
Abstract : A comprehensive understanding of the combustion characteristics of complex and changeable synthesis gas (syngas) compositions is essential for the further development of syngas-fueled engines with high thermal efficiency and low emissions. This study investigated explosion duration properties and laminar burning velocity (S L ) of multicomponent syngas/air using the pressure-rise method. The lean multicomponent syngas/air mixtures at various equivalence ratios (ϕ = 0.6, 0.7, and 0.8) containing different volumetric fractions of H2 (10–30%), CO (10–30%), and CH4 (40–60%) were conducted in a cylindrical constant volume combustion chamber using a dual-coil car ignition system. The explosion duration was characterized by the flame development time (FDT) and flame rising time (FRT), where FDT (FRT) is the time between spark ignition and 10% (10% and 90%) of the total heat release. The results showed that the values of FDT were approximately twofold of the FRT values, and they decreased with increasing H2 or CO content in the mixture. The leaner the mixture, the faster would be the reduction in the FRT and FDT as increasing H2 and/or CO content. Moreover, FDT and FRT were the shortest at a (H2 /(H2 +CO)) ratio of 0.5, at which the CH4 content was the lowest. Beyond this ratio, FDT and FRT increased, suggesting a significant effect of CH4 concentration. The shorter the FRT value, the higher would be the S L value. The current S L values, together with previous syngas data, could be well represented by a modified correlation with a slight discrepancy. This suggests a possible self-similar propagation of syngas/air laminar flames, regardless of the equivalence ratio, constituent fraction, temperature, pressure, and dilution. Additionally, a small value of mean absolute percentage error (~10.8%) revealed a better correlation for predicting S L values of syngas fuels.